MODIFICATIONS OF VOWELS IN CONNECTED SPEECH ("XXI ASRDA INNOVATSION TEXNOLOGIYALAR, FAN VA TAʼLIM TARAQQIYOTIDAGI DOLZARB MUAMMOLAR" nomli respublika ilmiy-amaliy konferensiyasi, 2024)
This article provides a comprehensive overview of the modifications that vowels undergo in connected speech, focusing on key processes such as vowel reduction, assimilation, coalescence, elision, and intrusion. It explores how these modifications contribute to the natural flow, rhythm, and efficiency of spoken language, highlighting their role in reducing articulatory effort and enhancing speech fluency. Through examples and explanations, the article demonstrates how vowels change in response to neighboring sounds, context, and speech rate. The piece emphasizes the importance of these modifications for language learners, suggesting that understanding and practicing them can improve both comprehension and pronunciation. This resource is valuable for those seeking to sound more native-like and achieve more effective, fluid communication in spoken English.